Clinical Trial Assessing the Efficacy of Gabapentin Plus B Complex (B1/B12) versus Pregabalin for Treating Painful Diabetic Neuropathy - Alberto Mimenza Alvarado; Sara Aguilar Navarro (Journal of Diabetes Research)
Introduction. Painful diabetic neuropathy (PDN) is a prevalent and impairing disorder. The objective of this study was to show the efficacy and safety of gabapentin (GBP) plus complex B vitamins: thiamine (B1) and cyanocobalamine (B12) compared to pregabalin in patients with moderate to severe intensity PDN. Method. Multicenter, randomized, blind study. Two hundred and seventy patients were evaluated, 147 with GBP/B1/B12 and 123 with PGB, with a 7/10 pain intensity on the Visual Analog Scale (VAS). Five visits (12 weeks) were scheduled. The GBP/B1 (100 mg)/B12 (20 mg) group started with 300 mg at visit 1 to 3600 mg at visit 5. The PGB group started with 75 mg/d at visit 1 to 600 mg/d at visit 5. Different safety and efficacy scales were applied, as well as adverse event assessment. Results. Both drugs showed reduction of pain intensity, without significant statistical difference (P=0.900). In the GBP/B1/B12 group, an improvement of at least 30% on VAS correlated to a 900 mg/d dose, compared with PGB 300 mg/d. Likewise, occurrence of vertigo was lower in the GBP/B1-B12 group, with a significant statistical difference, P=0.014. Conclusions. Our study shows that GPB/B1-B12 combination is as effective as PGB. Nonetheless, pain intensity reduction is achieved with 50% of the minimum required gabapentin dose alone (800 to 1600 mg/d) in classic NDD trials. Less vertigo and dizziness occurrence was also observed in the GBP/B1/B12 group. This trial is registered with ClinicalTrials.gov NCT01364298.